On possibility of separation of ²³⁹Pu and ²⁴⁰Pu contributions in emergency plutonium fallout of Chernobyl accident origin - Vodin, A.N.; Olejnik, S.N.; Rudak, E.A.; Ushakov, I.V.; Yachnik, O.I. (Вопросы атомной науки и техники, 2009)
The experiment-calculated method for separation of total α-activities of plutonium isotopes A(²³⁹Pu+²⁴⁰Pu) on partial activities A(²³⁹Pu) and A(²⁴⁰Pu) in emergency fallout of Chernobyl accident origin is developed.